2008
DOI: 10.1088/0741-3335/50/10/105005
|View full text |Cite
|
Sign up to set email alerts
|

Current and neutron scaling for megajoule plasma focus machines

Abstract: In a 2007 paper Nukulin and Polukhin surmised from electrodynamical considerations that, for megajoule dense plasma focus devices, focus currents and neutron yield Y n saturate as the capacitor energy E 0 is increased by increasing the capacitance C 0 . In contrast, our numerical experiments show no saturation; both pinch currents and Y n continue to rise with C 0 although at a slower rate than at lower energies. The difference in results is explained. The Nukulin and Polukhin assumption that the tube inductan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 19 publications
5
57
0
Order By: Relevance
“…The slightly higher yield compared with that in Table II is due to the reduced ratio "c" from 3.4 to 2.7. An earlier study has shown that reducing c, down to certain limits, has a beneficial effect in the case of neutron production operating in deuterium [24], and we have also confirmed through numerical experiments that this effect is also observed for neon Y sxr . The practical optimized results are shown in Fig.…”
Section: Optimizing For a Practical Optimum Configurationsupporting
confidence: 85%
See 1 more Smart Citation
“…The slightly higher yield compared with that in Table II is due to the reduced ratio "c" from 3.4 to 2.7. An earlier study has shown that reducing c, down to certain limits, has a beneficial effect in the case of neutron production operating in deuterium [24], and we have also confirmed through numerical experiments that this effect is also observed for neon Y sxr . The practical optimized results are shown in Fig.…”
Section: Optimizing For a Practical Optimum Configurationsupporting
confidence: 85%
“…The code has been used extensively in several machines including UNU/ICTP PFF [2]- [6], [14], [15], [19], NX2 [7], [16], [20], and NX1 [20], [21] and has been adapted for the Filippov-type plasma focus DENA [22]. A recent development is the inclusion of the neutron yield Y n using a beam-target mechanism [23]- [27], incorporated in recent versions [8] of the code (versions later than RADPFV5.13), resulting in realistic Y n scaling with I pinch [23], [24]. The versatility and utility of the model are demonstrated in its clear distinction of I pinch from I peak [28] and the recent uncovering of a plasma focus pinch current limitation effect [25], [26].…”
Section: Lee Model Code Incorporating Line Radiationmentioning
confidence: 99%
“…The code has been used extensively in several machines including UNU/ICTP PFF [2,7,8,10,11,[15][16][17], NX2 [9,12,18], and NX1 [18,19] and has been adapted for the Filippov-type plasma focus DENA [20]. A recent development is the inclusion of the neutron yield Y n using a beam-target mechanism [21][22][23][24][25], incorporated in recent versions [26,27] of the code (versions later than RADPFV5.13), resulting in realistic Y n scaling with I pinch [21,22]. The versatility and utility of the model are demonstrated in its clear distinction of I pinch from I peak [28] and the recent uncovering of a plasma focus pinch current limitation effect [23,24,29] as static inductance is reduced towards zero.…”
Section: Open Accessmentioning
confidence: 99%
“…The versatility and utility of the model are demonstrated in its clear distinction of I pinch from I peak [28] and the recent uncovering of a plasma focus pinch current limitation effect [23,24,29] as static inductance is reduced towards zero. Extensive numerical experiments had been carried out systematically resulting in the uncovering of neutron [21][22][30][31][32][33] and SXR [30][31][32][33][34][35][36][37] scaling laws over a wider range of energies and currents than attempted before. The numerical experiments also gave insight into the nature and cause of 'neutron saturation [31,33,38].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation